Cybersecurity measures for E-government frameworks - Zaman, Noor, 1972-; Shah, Imdad Ali, 1975-; Rajper, Samina, 1974- (Advances in electronic government, digital divide, and regional development., 2022)
"This book covers security issues that must be considered for E-governance applications, by helping and protecting them from possible cybersecurity attacks to alleviate the fraud potential as hackers use emerging technologies for cyber-attacks"--